2019
DOI: 10.1002/bse.2333
|View full text |Cite
|
Sign up to set email alerts
|

Innovation shock, outsourcing strategy, and environmental performance: The roles of prior green innovation experience and knowledge inheritance

Abstract: To investigate under what conditions an outsourcing strategy can show superior environmental performance, one stream of scholars has underscored the importance of prior green innovation experience, and another stream of scholars has underscored the importance of the in‐house possession of outsourced component knowledge. However, the empirical findings regarding the positive role of both scholarly streams when studied separately are mixed and sometimes contradictory. This study bridges these two distinct but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 73 publications
(118 reference statements)
3
24
0
Order By: Relevance
“…Green innovation may lead firms to find new ways of incorporating waste into saleable products that provide additional revenue (Bassetti et al, 2021). Thus, successful green innovation helps firms to increase efficiency and strengthen their core competences, which may eventually improve their economic performance (Khurshid et al, 2019).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Green innovation may lead firms to find new ways of incorporating waste into saleable products that provide additional revenue (Bassetti et al, 2021). Thus, successful green innovation helps firms to increase efficiency and strengthen their core competences, which may eventually improve their economic performance (Khurshid et al, 2019).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…First, extant studies have failed to examine the underlying mechanism through which HR slack influences environmental performance in SMEs. Our paper, in contrast, sought to obtain evidence relevant to this question by investigating the potential role of sustainable innovation, which is strongly related to environmental performance (Carrión‐Flores & Innes, 2010; Khurshid, Park, & Chan, 2019; Long et al, 2017). This is an important line of inquiry because understanding the mechanism through which firm resources influence environmental performance in emerging markets is a crucial task because SMEs often lack resources to undertake environmental activities (Earnhart, Khanna, & Lyon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yenipazarli, Vakharia and Bala (2020) highlight that eco-innovation in the use stage not only improves the environmental performance of the product in use, but it also increases product value for consumers by reducing the cost of use. Khurshid, Park and Chan. (2019) suggested that previous experience in ecoinnovation and knowledge on outsourcing play an important role in improving environmental performance.…”
Section: Moderation Of Institutional Mimicry On Eco-innovation Perfor...mentioning
confidence: 99%